2020
DOI: 10.34172/bi.2021.32
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle arrest and anti-cancer potential of probiotic Lactobacillus rhamnosus against HT-29 cancer cells

Abstract: Introduction: Nowadays, probiotic bacteria have been considered as a factor in the prevention and treatment of cancer, especially by induction of apoptosis. This study aimed to evaluate the cytotoxic, anti-proliferative, and apoptotic effects of the supernatant of probiotic Lactobacillus rhamnosus on HT-29 cell line. Methods: Molecular identification of probiotic L. rhamnosus was carried out using specific primers of 16S rRNA gene and sequencing. HT-29 cells were treated with different concentrations of bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 42 publications
3
23
0
1
Order By: Relevance
“…First, Lactobacillus rhamnosus modulates homeostasis of the intestinal flora and protects the mucosa and restores the intestinal barrier function by enhancing the expression of genes related to healthy intestinal permeability (62)(63)(64), whereas the homeostatic effect of intestinal flora on gynecological malignancies has been mentioned above. Secondly, regarding human selfprotection, Lactobacillus rhamnosus potentially regulates immunity, causing apoptosis of cancer cells and anti-inflammatory effects by activating or inhibiting cytokine expression (65)(66)(67), and invasion of pathogens (68,69). Eventually, Lactobacillus rhamnosus also protects the body from the toxicity and side effects of radiotherapy and other treatment methods (70,71).…”
Section: Lactobacillus Rhamnosusmentioning
confidence: 99%
“…First, Lactobacillus rhamnosus modulates homeostasis of the intestinal flora and protects the mucosa and restores the intestinal barrier function by enhancing the expression of genes related to healthy intestinal permeability (62)(63)(64), whereas the homeostatic effect of intestinal flora on gynecological malignancies has been mentioned above. Secondly, regarding human selfprotection, Lactobacillus rhamnosus potentially regulates immunity, causing apoptosis of cancer cells and anti-inflammatory effects by activating or inhibiting cytokine expression (65)(66)(67), and invasion of pathogens (68,69). Eventually, Lactobacillus rhamnosus also protects the body from the toxicity and side effects of radiotherapy and other treatment methods (70,71).…”
Section: Lactobacillus Rhamnosusmentioning
confidence: 99%
“…From the literature data, it is evident that intestinal cells are the most common research model on this topic, due to the fact that probiotics and the products of their metabolism (postbiotics) interact with the intestinal epithelium after reaching the intestines. Many authors have investigated the antiproliferative and cytotoxic activity of LAB postbiotics against colon adenocarcinoma cell lines, such as Caco-2, SW-480, CT26, HRT-18, or HT-29 [ 9 , 10 , 11 , 29 , 30 , 31 , 32 , 33 , 34 ]. The concentrations of the PFM are the most often given as a percentage or mg/mL, less often in µg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of the PFM are the most often given as a percentage or mg/mL, less often in µg/mL. The range of the tested concentrations is from 0.47% to 100% [ 11 , 35 , 36 , 37 , 38 , 39 ] or from 0.0001 to 1000 mg/mL [ 18 , 29 , 31 , 34 , 40 , 41 ]. In all of the above-mentioned studies, the MTT assay dominates as a tool of antiproliferative activity testing for cancerous cell lines and cytotoxicity assayed to normal cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using various cancer model studies, it has been demonstrated that a healthy gut ora has a strong in uence on the e cacy of anticancer drugs such as cyclophosphamides (CTX) and immune checkpoint inhibitors (ICIs) [38][39][40][41]. The current study compares to any of the marketed probiotic formulations, such as L. rhamnosus, which are known to inhibit cancer cell growth in a dose-and time-dependent manner [42]. It also compares to L. rhamnosus GG, the most studied microbe model in cancer, in terms of potentiating the gut microbiota and protecting against tumor genesis [36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%